From Breathlessness to Better Living: Transforming COPD Care with Home-Based Pulmonary Rehabilitation - Abins Thozhuthinkal Kasim; Ravi Gaur; Nitesh Manohar Gonnade; Nagma Sheenam; Chinchu Kolakkanni; Sarankumar Ganesan; Adharshna Thangamalai Kannan (Rambam Maimonides Medical Journal)
Background Chronic respiratory diseases, such as chronic obstructive pulmonary disease (COPD), significantly impact patients’ quality of life by limiting physical function, mobility, and overall well-being. Pulmonary rehabilitation (PR), particularly home-based programs, has emerged as a vital non-pharmacological intervention to address these limitations. However, comprehensive assessments of the impact of home-based PR on both lung function and disability in COPD patients remain limited. Objective This study aimed to evaluate the effectiveness of a 12-week home-based PR program on pulmonary function and disability in COPD patients, using pulmonary function tests (PFTs) and the World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) to assess outcomes across multiple domains. Methods A prospective, single-arm pre–post interventional study was conducted among 62 COPD patients at All India Institute of Medical Sciences, Jodhpur. Participants completed a 12-week home-based PR program, which included endurance exercises, breathing techniques, and self-management education. Pulmonary function tests were conducted, and disability levels were assessed using WHODAS 2.0 at baseline and after completing the program. Results Improvements were observed in pulmonary function, with forced vital capacity (FVC), and forced expiratory volume in one second (FEV1), showing substantial increases (FVC: 2.50±0.43 L to 2.85±0.59 L; FEV1: 1.53±0.33 L to 1.63±0.34 L; P<0.001). The WHODAS 2.0 scores demonstrated notable reductions in disability, particularly in the life activities and participation domains (P<0.001). Cognitive and self-care scores remained stable, while improvements in mobility were observed but not significant. Regression analysis revealed a strong negative correlation between increases in FVC and reductions in WHODAS 2.0 total scores (r=−0.65), highlighting FVC as a key predictor of disability reduction. Conclusion The 12-week home-based PR program improved lung function and reduced disability in COPD patients. These findings support the role of home-based PR as a viable, patient-centered alternative to traditional rehabilitation, addressing both physical and social dimensions of health. Future research should focus on long-term outcomes, the potential for broader implementation, and expanding access to underserved populations.